Integrated Risk Assessment Model Based on Unstable Fuzzy Linguistic Terms in Occupational Health and Safety: Application in Machinery Sector in Turkey - Duruel, Turgay; Gulsun, Bahadir (WORLD SCIENTIFIC PUBL CO PTE LTD, 2025)
Nowadays, the field of occupational health and safety has emerged as a key subject of scientific research for nations. The well-being and safety of individuals are of utmost importance in all aspects of professional life. The goal of occupational health and safety is to optimize the physical and emotional well-being of employees. To accomplish these objectives, nations implement numerous laws and regulations. The rules published in Turkey are mostly based on the European Community 89/391 Directive, which is known as the Framework Directive on Taking Measures to Improve the Health and Safety of Workers. One of these regulations is the Risk Assessment Regulation, which is the most crucial argument in the field of occupational safety. In this study, for the first time in the literature, a specialized group of experts called the risk assessment team was formed according to the regulations. Based on the extension of fuzzy sets using vague linguistic terms, a comprehensive risk assessment model was proposed by integrating multi-criteria decision-making methods such as SWARA, ARAS, AHP, CRITIC, and Visual PROMETHEE. Furthermore, the risks were ranked in terms of their importance using the ARAS method, which uses ambiguous linguistic terms to assess the risks. The most commonly used risk assessment methods in the machinery industry, such as Fine-Kinney, FMEA, and the 5 x 5 Matrix, were used to evaluate the same risks based on the collective opinion of experts. The rankings obtained were then consolidated into a single sequence using the Borda count method. Later on, a comparison of risk rankings was conducted using the proposed model, followed by a correlation analysis. The correlation analysis produced a result of 0.744, indicating a high correlation. This result demonstrated the applicability of the suggested method in the field of occupational health and safety. Moreover, the data obtained using triangular fuzzy numbers and the data obtained using a five-point scale were ranked according to their importance levels using the Visual PROMETHEE application. Finally, the cross-validation of these ranking results was ensured. The results were visually evaluated in the PROMETHEE-GAIA framework, considering the relationships between alternative measures and risks.
Keywords: Occupational health and safety; undecided fuzzy linguistic terms; SWARA; ARAS; Visual PROMETHEE; AHP; ANALYTICAL HIERARCHY PROCESS; DECISION-MAKING; FAILURE MODE; PERFORMANCE; MANAGEMENT; SELECTION; CONSTRUCTION; FMEA; Engineering